TATA KELOLA PEMERINTAHAN DESA PADA PERBEDAAN INDEKS DESA MEMBANGUN (IDM): STUDI TIGA DESA DI KABUPATEN MALANG - Setyowati, Eka (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Development in the village is very important, because the majority of Indonesian citizens live in rural areas. So far Kemendesa has not seen any governance factors in assessing IDM differences in a village. Kemendesa only sees in terms of economic, social and environmental factors. This study aims to look at the extent to which governance factors in producing different village indexes develop. The results of the study indicate that there is a positive contribution to the factors of village governance towards the final results of the village index building. This can be seen in terms of the factors of the government of the Tumpang Village, Malangsuko Village and Pulungdowo Village, both involving the village community in the policy making process, for example in the preparation of the Regional Budget, Making Village Regulations or other activities. But the fundamental differences between the three villages are at different levels of community participation. In the village, overlapping communities is more participatory compared to the villages of Malangsuko and Pulungdowo.